EFFORT GURU PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM PENANAMAN SIKAP SOPAN SANTUN PASCAPEMBELAJARAN DARING SISWA KELAS 8 DI SMPN 1 SILIRAGUNG - Zuyyina Rosy Paradise; Arief Ardiansyah; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Effect of onlie teaching and learning process that cause polite behaviour decrease to parents and teachers can’t monitor students’ behaviour , teachers can’t teach polite behaviour as teaching and learnig process in the classroom. To increase the students’ polite behaviour decrease, an Islamic religious teacher must do effort to make better. The role of Islamic religious teacher as one of the pioneers in the success on students’ personality development. The researcher formulate the problem about strategy and factors that influence Islamic religious teacher on the students’ polite behaviour at grade 8 at SMPN 1 Siliragung-Banyuwangi. The goal of this research is to describe effort and factor that influence Islamic religious teacher and character in teaching the students’ good character at grade 8 students at SMPN 1 Siliragung- Banyuwangi. The researcher use qualitative approach (case study). The reseacrher use data collecting technique (observation, intervew and documentation ). The result of the research are (a) the strategy of Islamic religious teacher and character in teaching polite behaviour idest; Giving comprehesion and model, doing habitual action and also advise; (b) the supporting factors in teaching polite behaviour after study idest; The active role of the teacher,activity or institution program,students’ realize and the collaborate with students’ parents. The obstacle factors idest: the background of the family, assooociation addictive gadget.